A VALUABLE SOURCE FOR STUDYING THE HISTORY OF THE FERGANA VALLEY IN BAHR AL-ASRĀR FĪ MANĀQIB AL-AKHYĀR - Musayev Azizbek Baxridinovich (Modern American Journals, 2025)
This article discusses Bahr al-asrār, a valuable historical work by Mahmud ibn Vali that provides significant information about the Bukhara Khanate from the early 17th century up to the 1640s. The fact that the source has not yet been fully translated into any language and that its most valuable part exists in a single manuscript copy underscores the need to introduce the work more broadly into academic circulation. Furthermore, the detailed coverage of political developments in the Fergana Valley during this period further enhances the scholarly value of the text.
Keywords: Mahmud ibn Vali, Bahr al-asrār, Bukhara Khanate, Fergana Valley, Ashtarkhanids, Shaybanids